Tuberculosis arthritis of the ankle mimicking a talar osteochondritis. (December 2021) - Hanène, Ferjani; Nacef, Lilia; Maatallah, Kaouther; Triki, Wafa; Kaffel, Dhia; Hamdi, Wafa
Highlights: Osteoarticular Tuberculosis (OT) of the foot is extremely rare with an incidence rate of 4–8%. Clinical findings are not specific with fever, pain, swelling and limitation. Plain radiographs and CT scan may mislead to differential diagnosis, in this case, osteochondritis of the talus. MRI is currently the mainstay imaging tool of OT. Abstract: Tuberculosis arthritis of the ankle accounts for 10% of all cases of osteoarticular tuberculosis (OT). Because of its rarity and insidious symptoms, diagnosing it may be challenging. Furthermore, its imaging findings mimic those of other diseases. The case of ankle tuberculosis arthritis misdiagnosed as talus necrosis is reported. The difficulties faced by clinicians when confronting such situations are also illustrated.